Flower-visiting lizards as key ecological actors for an endemic and critically endangered plant in the Canary Islands - González-Castro, Aarón; Siverio, Felipe (Journal of Pollination Ecology, 2024)
Oceanic islands are places where biological assemblages are relatively simple, as compared to the mainland. On islands, however, pollinator assemblages may to be composed of a taxonomically disparate group of organisms (e.g. insects, lizards, and birds), some of them with opportunistic nectar-feeding behaviour. Here we investigated some components of pollination effectiveness of Lotus maculatus (Fabaceae), an endangered Canary Islands endemic. In a flower exclusion experiment, we bagged flowers and compared their subsequent fruit and seed set to that of control flowers. Number of interactions with vertebrate and invertebrate flower visitors was counted and it was recorded whether interactions were legitimate (potentially pollinating) or non-legitimate (nectar robbing). Additionally, we estimated pollen loads on lizards and looked for any relationship between reproductive success of individual plants and number of visits made by the top three flower-visiting species (in terms of both frequency of occurrence at censuses and number of floral visits). Bagged flowers fruited less and with fewer seeds than control flowers. The only observed flower-visiting vertebrate was the Tenerife lizard Gallotia galloti, whose interactions were always legitimate and with around a half of captured individuals carrying pollen grains. The most frequent flower-visiting insect was the honeybee Apis mellifera followed by the solitary bee Lasioglossum arctifrons. The honeybee, however, was only a nectar robber, and the solitary bee was not an effective pollinator, but rather a pollen gatherer. Fruit set by individual plants was positively related only to frequency of visits by the lizard. Thus, the lizard seems to play a key role in the conservation management of L. maculatus.